2019
DOI: 10.1088/1755-1315/315/4/042013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the phagocytizing blood cells functional activity of cattle (Bous Taurus)

Abstract: Reactions of free radicals’ formation are integral parts of many metabolic processes in the body, but in a number of states under the influence of external and internal factors there occurs intensification of these reactions accompanied by excessive generation of phagocytizing blood cells activity (PBCA), therefore the study of the antioxidant activity of biological fluids is of clinical (diagnostic, predictive) value. The component analysis of the blood chemiluminescent kinetics of Bous Taurus of different ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
0
1
Order By: Relevance
“…Johnson et al [12] preliminary findings demonstrated that camel neutrophils exhibited a higher CL response than sheep. In contrast to our findings, Cooray et al [31] described no significant difference in the kinetic luminol-dependent CL response of camel neutrophils isolated from blood compared to those of humans and cows [32,33].…”
Section: Luminol-dependent CLcontrasting
confidence: 99%
“…Johnson et al [12] preliminary findings demonstrated that camel neutrophils exhibited a higher CL response than sheep. In contrast to our findings, Cooray et al [31] described no significant difference in the kinetic luminol-dependent CL response of camel neutrophils isolated from blood compared to those of humans and cows [32,33].…”
Section: Luminol-dependent CLcontrasting
confidence: 99%